Determining the Relationship Between Feeding Patterns and Stunting Incidence in Children: A Cross-Sectional Study in Magetan, Indonesia - Sulikah Sulikah; Tyas Arini; Nurweningtyas Wisnu; Aini Ahmad (International Journal of Advanced Health Science and Technology, 2024)
Stunting has the potential to slow brain development and increase the risk of chronic disease. Panekan District is an area with the highest prevalence of stunting in Magetan Regency. This study aims to determine the effect of feeding patterns on the incidence of stunting in children aged 1-5 years. This research is a cross-sectional analytic observational study. Samples were taken using proportional random sampling technique so that a total of 217 mothers with stunted children aged 1-5 years were obtained. Primary data collection used the Child Feeding Questionnaire and secondary data used the EPPGBM application. The results of the Chi-square test can be concluded that the significant value is 0.000 <0.05, the significant value of frequency is 0.027 <0.05, the significant value of the number of meals is 0.016 <0.05. Based on the description above, it can be concluded that there is an influence on the pattern of feeding on the incidence of stunting, so it is recommended that parents use KIA’s books to increase knowledge and observe about the growth and development of their children and always apply the right feeding pattern for their children from birth to adulthood because nutritional intake is one of the important factors to create a healthy and quality life.